2014
DOI: 10.1038/nn.3863
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and treatment for learning and memory deficits in mouse models of Noonan syndrome

Abstract: In Noonan Syndrome (NS) 30% to 50% of subjects show cognitive deficits of unknown etiology and with no known treatment. Here, we report that knock-in mice expressing either of two NS-associated Ptpn11 mutations show hippocampal-dependent spatial learning impairments and deficits in hippocampal long-term potentiation (LTP). In addition, viral overexpression of the PTPN11D61G in adult hippocampus results in increased baseline excitatory synaptic function, deficits in LTP and spatial learning, which can all be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(211 citation statements)
references
References 36 publications
13
193
4
1
Order By: Relevance
“…Consequently, mice could learn the task at a rapid pace and reached 75.2% average accuracy by session 6. This experimental period is quite short, even when compared with that of other behavioral tasks, such as the Morris water maze test, which is a widely used spatial memory task and that takes about 7 days (D'Hooge & De Deyn 2001; Vorhees & Williams 2006;Lee et al 2014). Therefore, this simplified task can be used as a timesaving touchscreen PAL task to test object-location memory in a simple manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, mice could learn the task at a rapid pace and reached 75.2% average accuracy by session 6. This experimental period is quite short, even when compared with that of other behavioral tasks, such as the Morris water maze test, which is a widely used spatial memory task and that takes about 7 days (D'Hooge & De Deyn 2001; Vorhees & Williams 2006;Lee et al 2014). Therefore, this simplified task can be used as a timesaving touchscreen PAL task to test object-location memory in a simple manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the cases in which simpler PAL tests may be more suitable, we developed a simplified form of sPAL. Our goal in doing this was to make a touchscreen PAL task that requires a similar period of time as the Morris water maze test (Vorhees & Williams 2006;Lee et al 2014). Finally, we tested whether the PAL tasks with the new protocols are hippocampus dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has become increasingly clear that molecules in the RAS-MAPK pathway are essential for normal neurophysiologic functioning within multiple brain circuits (Samuels et al 2009), including those involved in learning and memory (Costa et al 2001;Pagani et al 2009). Lee et al (2014) recently demonstrated that mice expressing either of two NS-associated mutations in PTPN11 show hippocampaldependent impairments in spatial learning tasks as well as deficits in hippocampal long-term potentiation. Other studies have reported that dysregulation of Ras can result in differences in maturation or functioning of frontal-subcortical circuitry involved in attention and cognitive control (Shilyansky et al 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Molecules in the RAS-MAPK pathway are known to be essential for regulating brain plasticity, including processes necessary for memory stability (Davis and Laroche 2006). Animal models have demonstrated that mutations mimicking those in NS result in deficits in long-term memory formation in the hippocampus or analogous regions and are associated with learning deficits (Pagani et al 2009;Lee et al 2014). As a result, there has been increased attention in trying to understand whether learning deficits may be reversed or attenuated using pharmacological treatments or alternative learning methods that capitalize on our understanding of the mechanisms interfering with memory encoding and consolidation.…”
Section: Memorymentioning
confidence: 99%
See 1 more Smart Citation